Dosimetry of indigenously developed 177Lu patch source for surface brachytherapy—Experimental and Monte Carlo methods. (20th December 2018) - Sahoo, Sridhar; Shrivastava, Vandana; Selvam, T Palani; Bakshi, A K; Kumar, Rajesh; Rama, P; Datta, D; Chinnaesakki, S; Saxena, S K; Kumar, Yogendra; Dash, A
Abstract: This paper describes the evaluation of dosimetry characteristics of an in-house developed 177 Lu skin patch source for treatment of non-melanoma skin cancer. A 177 Lu skin patch source based on Nafion-115 membrane backbone containing 3.46 ± 0.01 mCi of activity was used. Activity measurement of the patch source was based on gamma ray spectrometry using a HPGe detector. The efficiencies of the HPGe detector were fitted using an orthogonal polynomial function. The absorbed dose rate to water at 5 μ m depth in water was determined using an extrapolation chamber, EBT3 Gafchromic film and compared with Monte Carlo methods. The correction factors such as Bragg-Gray stopping power ratio of water-to-air and chamber wall material being different from water, needed to be applied on measurements for establishing the dose rate at 5 μ m depth, were calculated using the Monte Carlo method. Absorbed dose rate at 5 μ m depth in water (surface dose rate) measured using an extrapolation chamber and EBT3 Gafchromic film were 9.9 ± 0.7 and 8.2 ± 0.1 Gy h −1 mCi −1 respectively for the source activity of 3.46 ± 0.01 mCi. The surface dose rate calculated using the Monte Carlo method was 8.7 ± 0.2 Gy h −1 mCi −1, which agrees reasonably well with measurement. The measured dose rate per mCi offers scope for ascertaining treatment time required to deliver the dose for propitious therapeutic outcome. Additionally, on-axis depth dose and lateral dose profiles at 5 μ m and 1 mm depth in water phantom were also calculated using the Monte Carlo method.